Mapping the Structure, Composition, Properties and Dental Erosion in Human Enamel - Low, It-Meng; Alhuthali, Abdullah; Duraman, Nora (Nova Science Publishers Inc., 2010)
The structure-property relationship and dental erosion in human dental enamel composites is reviewed. The phase composition, microstructure and mechanical properties as characterized by grazing-incidence synchrotron radiation diffraction, atomic-force microscopy, scanning electron microscopy and Vickers indentation are described and discussed. The existence of distinct graded changes in crystal disorder, phase abundance, crystallite size and hardness within these enamel ceramics is highlighted. The phenomenon of load-dependent hardness in enamel but load-independent hardness in the dentine is highlighted and discussed. An in-situ monitoring technique of dental erosion in tooth enamel ceramics when immersed in soft-drinks is described. Atomic absorption results suggest that the increasing weight loss in tooth enamel during dental erosion in soft drinks can be attributed to the continuous leaching of Ca2+ ions, in addition to phosphorus, oxygen, and hydrogen. The effect of dental erosion on the hardness of enamel is also discussed.